2006
DOI: 10.2174/092986706776360987
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Dysfunction in Aging: Potential Effects of Resveratrol, an Anti- Inflammatory Phytoestrogen

Abstract: Epidemiological studies demonstrated that even in the absence of other risk factors (e.g. diabetes, hypertension, hyperhomocysteinemia, hypercholesterolemia), advanced age itself significantly increases cardiovascular morbidity by enhancing vascular oxidative stress and inflammation. Because the population in the Western world is rapidly aging, there is a substantial need for pharmacological interventions that delay the functional decline of the cardiovascular system. Resveratrol is an atoxic phytoestrogen fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
88
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(100 citation statements)
references
References 98 publications
(117 reference statements)
5
88
0
6
Order By: Relevance
“…Caloric restriction (CR) is an intervention that attenuates many effects of aging (Anderson and Weindruch 2010;Labinskyy et al 2006;Leeuwenburgh and Prolla 2006), including cardiovascular morbidity (van der Loo et al 2000), cross-linking of cardiac and skeletal muscle proteins (Leeuwenburgh et al 1997), mitochondrial dysfunction (Aspnes et al 1997;Payne et al 2003), loss of skeletal muscle mass (Payne et al 2003;van der Loo et al 2000), and endothelial dysfunction (Barja 2002;Castello et al 2005;Gredilla et al 2004;Gredilla et al 2001;Taddei et al 2006). Furthermore, CR attenuates the age-related impairment of the NO signaling system (Minamiyama et al 2007;Sharifi et al 2008;Yang et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Caloric restriction (CR) is an intervention that attenuates many effects of aging (Anderson and Weindruch 2010;Labinskyy et al 2006;Leeuwenburgh and Prolla 2006), including cardiovascular morbidity (van der Loo et al 2000), cross-linking of cardiac and skeletal muscle proteins (Leeuwenburgh et al 1997), mitochondrial dysfunction (Aspnes et al 1997;Payne et al 2003), loss of skeletal muscle mass (Payne et al 2003;van der Loo et al 2000), and endothelial dysfunction (Barja 2002;Castello et al 2005;Gredilla et al 2004;Gredilla et al 2001;Taddei et al 2006). Furthermore, CR attenuates the age-related impairment of the NO signaling system (Minamiyama et al 2007;Sharifi et al 2008;Yang et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol has been identified in more than 70 species of plants, including grapevines (Vitis vinifera), mulberries (Morus rubra), Vaccinum species, and peanuts (Arachis hypogea), and it is thought to have diverse antiatherogenic activities (42, 55-57, 60, 61), such as the inhibition of LDL oxidation (22) and platelet aggregation (46) and regulation of vascular smooth muscle proliferation (24 -26, 54). Recently, studies from this and other laboratories have shown that resveratrol inhibits endothelial activation and monocyte adhesion (12, 21, 39) and attenuates proinflammatory gene expression by inhibition of NF-B activation in coronary arterial endothelial cells (12).There is overwhelming evidence that oxidative stress plays a crucial role in the development of vascular disease and vascular aging (11,13,35). The mechanisms by which oxidative stress elicits endothelial cell injury during atherogenesis are likely to include induction of inflammatory processes (11) and activation of cellular apoptotic pathways (9).…”
mentioning
confidence: 99%
“…There is overwhelming evidence that oxidative stress plays a crucial role in the development of vascular disease and vascular aging (11,13,35). The mechanisms by which oxidative stress elicits endothelial cell injury during atherogenesis are likely to include induction of inflammatory processes (11) and activation of cellular apoptotic pathways (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is in addition to increased scavenging of ROS, increased NO synthase activity, reduced platelet aggregation, angiogenesis activity and anti-apoptosis activity. (120)(121)(122)(123)(124)(125)(126)(127)(128)(129) As an example, SIRT1 regulates the activity of PGC-1a, a central factor in controlling energy state and contractile function in cardiac muscle. (130) SIRT1-induced angiogenic activity is probably mediated via FOXO transcription factors that regulate blood vessel endothelial development.…”
Section: Sirtuin Class O Of Forkhead Box Transcription Factors (Foxomentioning
confidence: 99%